A Globally Distributed Cyanobacterial Nitroreductase Capable of Conferring Biodegradation of Chloramphenicol - Qiu-Lian Zhong; Jiu-Qiang Xiong (Research)
Cyanobacteria play pivotal roles in global biogeochemical cycles and aquatic ecosystems due to their widespread distribution and significant contributions to primary production. Yet, the interactions between cyanobacteria and antibiotics remain unclear. This study revealed that Synechocystis sp., a cyanobacterial species, removed 94.27% of 0.1 mg l−1 chloramphenicol (CAP) through enzyme-mediated degradation. While cytochrome P450 enzymes (CYP450s) were found unnecessary for CAP removal, a gene encoding cyanobacterial nitroreductase was significantly up-regulated (7.85-fold) under CAP exposure. The purified nitroreductase exhibited strong binding affinity to CAP (Kd = 2.9 nM) and a Michaelis constant (Km) of 104.0 μM. By engineering a bacterial strain with nitroreductase, 94.43% of 0.1 mg l−1 CAP was removed within 2 h. Metagenomic and metatranscriptomic analyses showed that nitroreductase genes and transcripts are globally distributed across diverse microbial phyla. These findings uncover a novel enzyme for CAP degradation and advance sustainable biotechnologies to mitigate antibiotic pollution, addressing critical environmental challenges in aquaculture and other industries globally.